Implementation of the Just In Time Method to Efficient Production Costs (Literature Review Study) - Gita Shyntia Lumbantobing; Putri K Nasution (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2023)
In production activities, the problem of inventory is one thing that must be considered in order to avoid waste in the production process. This study shows the control of raw material inventory in a production to get the optimal level of inventory. The just in time (JIT) method reduces the amount of inventory so that it can reduce costs as efficiently as possible. Inventory control with the just in time (JIT) method is the development of the economic order quantity (EOQ) method by reducing shipping lots. Based on this research, it is known that with the same data, using just in time (JIT) the costs incurred are smaller than the costs incurred previously. Costs previously incurred were Rp. 14,019,680.00 using economic order quantity (EOQ) the costs incurred were Rp. 8,497,593,00 while using just in time (JIT) the costs incurred were Rp. 3,800,239, 00 From these results it can be seen that with the just in time (JIT) method the production costs incurred are more efficient. The solution using the just in time (JIT) method is done with the help of MATLAB software.